Gene therapy for liver regeneration: Experimental studies and prospects for clinical trials - Atta, Hussein M (Baishideng Publishing Group Co., Limited, 2010)
The liver is an exceptional organ, not only because of its unique anatomical and physiological characteristics, but also because of its unlimited regenerative capacity. Unfolding of the molecular mechanisms that govern liver regeneration has allowed researchers to exploit them to augment liver regeneration. Dramatic progress in the field, however, was made by the introduction of the powerful tool of gene therapy. Transfer of genetic materials, such as hepatocyte growth factor, using both viral and non-viral vectors has proved to be successful in augmenting liver regeneration in various animal models. For future clinical studies, ongoing research aims at eliminating toxicity of viral vectors and increasing transduction efficiency of non-viral vectors, which are the main drawbacks of these systems. Another goal of current research is to develop gene therapy that targets specific liver cells using receptors that are unique to and highly expressed by different liver cell types. The outcome of such investigations will, undoubtedly, pave the way for future successful clinical trials.